From "participation" to "rights and responsibilities" in forest management: workable methods and unworkable assumptions in West Kalimantan, Indonesia - Colfer, C.J.P.; Wadley, R.L. (Resources for the Future and Center for International Forestry Research, 2001)
This chapter reports the results of research in West Kalimantan, Indonesia, originally designed to assess quickly and easily the level and nature of participation by local people in forest management. The authors briefly describe pertinent results from their assessment methods. Although the functions initially anticipated for participation are not wrong, they reflect a way of looking at forest management that were concluded needs rethinking. In the discussion of the change needed, Jordan’s concept of “authoritative knowledge” and “social” or “cultural capital” was used. The authors also suggest substituting “rights and responsibilities to manage the forest cooperatively” for “participation” in places like Danau Sentarum Wildlife Reserve (DSWR). Important remaining policy-related issues include the variations in quality of local management systems, values held by the different stakeholders, and potential productivity of individual systems. Finally it concludes that, given the dynamism and complexity that characterise natural forests and their inhabitants, cooperation among all stakeholders in an ongoing dialogue is most likely the only way that sustainable forest management can in fact occur.